Photovoltaic Roofing for Motorways and Other High-Ranking Road Networks: Technical Feasibility, Yield Estimation, and Final Demonstrator - Rita Ebner; Christoph Mayr; Marcus Rennhofer; Karl A. Berger; Martin Heinrich; Felix Basler; Andreas J. Beinert; Jonas D. Huyeng; Manfred Haider; Dominik Prammer; Alois Vorwagner; Markus Fehringer; et al. (Energies)
As renewable energies need to be extended massively, new concepts are necessary to prevent land conflicts with other uses. Such concepts should have a high generality to offer a swift expansion of renewables anywhere. Within the project, the Photovoltaic Road Roofing Concept (PV-SÜD), a concept for the roofing of roadways with solar panels, was investigated. Its effects on the road infrastructure were analyzed, and a demonstrator was built. The technical boundary conditions and requirements resulting from the specific application type were determined regarding the photovoltaic technology, the possible energy generation, and the supporting structure. The study was completed for a technical solution of 10 m length, 17 m width, and 6.8 m height, with the option of a pent roof (highways running east–west) or gable roofs (highways running north–south). The main target aim was to investigate the potential for widespread use at any site, in contrast to previous studies which mainly aimed at a singular site or demonstrator project. The final solution can support a 38.5 kWp photovoltaic system with a specific annual yield of between 37.5 MWh and 44.0 MWh. The yield variation in sites in Austria and Germany was 14.7% and 17.9%, respectively. One demonstrator roofing was realized as a steel-frame construction with active glass–glass photovoltaic technology at a highway in Hegau (GE).